End of the Land - Shafi'i, Malek
Verzio FF Submission The story of Afghan refugees traveling to Iran and the Netherlands on September 11th, 2001 and their subsequent repatriation to Afghanistan after the fall of the Taliban regime. A film about the impact of 9/11 on the lives of Afghan refugees.